2008
DOI: 10.1002/cncr.23390
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for high‐risk early‐stage epithelial ovarian cancer

Abstract: BACKGROUND. The purpose was to identify the factors predictive of recurrence and survival in patients with high‐risk (stage I, grade 3; stage IC, stage II, or clear cell) epithelial ovarian cancer after adjuvant therapy. METHODS. Data was extracted from patients who underwent primary surgery followed by adjuvant therapy in 2 randomized trials by the Gynecologic Oncology Group (Protocols 95 and 157). Kaplan‐Meier survival estimates and Cox proportional hazards model adjusted for covariates were used for analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
89
3
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(104 citation statements)
references
References 60 publications
7
89
3
5
Order By: Relevance
“…FIGO-stage was the strongest predictive factor for recurrent disease in this study and this has been confirmed by studies on patients in FIGO-stages I-II both after complete surgical staging (1,27) and apparent staging (5). However, the fact, that p53 status and p53/bax status both were independent prognostic factors for DFS in multivariate analysis was the most striking finding noted in our study.…”
Section: Discussionsupporting
confidence: 89%
“…FIGO-stage was the strongest predictive factor for recurrent disease in this study and this has been confirmed by studies on patients in FIGO-stages I-II both after complete surgical staging (1,27) and apparent staging (5). However, the fact, that p53 status and p53/bax status both were independent prognostic factors for DFS in multivariate analysis was the most striking finding noted in our study.…”
Section: Discussionsupporting
confidence: 89%
“…Thirteen percent cases were well-differentiated tumours and the rest were either moderately or poorly differentiated which correlates well with other studies. Studies in the published literature differ on the prognostic importance of tumour grade as a predictor of survival [2,16]. Tumour grade was not an independent predictor of survival in our study.…”
Section: Discussioncontrasting
confidence: 75%
“…Nulliparity was an independent predictor in various studies [16]. This was true of our study as 78 % of these cases were nulliparous.…”
Section: Discussionsupporting
confidence: 47%
“…However, disagreement will always exist on tumors with borderline grades and, unless a tumor is judged unquestionably within a grade, the grade assigned is an This is controversial. Whereas some studies found that intraoperative capsule rupture portends a higher risk of disease recurrence [22,24], others did not [17,18,21,25,26]. In a multivariable analysis, capsule rupture and positive cytologic washings remained M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 12 independent predictors of worse disease-free survival [24].…”
Section: Does Histologic Grade Influence Prognosis Of Stage I Tumors?mentioning
confidence: 89%